Make your own history : documenting feminist and queer activism in the 21st century - Bly, Lyz; Wooten, Kelly (Litwin Books series on gender and sexuality in information studies ;, 2012)
Make Your Own History: Documenting Feminist and Queer Activism in the 21st Century addresses the practical and theoretical challenges and advantages of researching, documenting, and archiving recent and contemporary activists in the feminist and queer movements. In the last few decades, the place and practice of activism has shifted from a physical "headquarters" where activists convene to plan and strategize, to the reality where planning happens at various desks and kitchen tables across the country (or world) and activists then convene at one site for an action (the prime example of this being the WTO protest in Seattle in 1999). So much of the work is taking place in the digital environment and/or within smaller do-it-yourself (DIY) and anarchist subcultures where ideas are often shared via zines and other ephemeral materials. The challenge of the archivist and the scholar, whose work is traditionally paper-based, is to keep up with the changing modes of communication of these individuals and organizations and to make sure these activists' work is not left out of the historical record